2019
DOI: 10.1177/1534735418823266
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Oncology: International Perspectives

Abstract: Interest in integrative oncology (IO) is growing globally. Patients with cancer are actively using traditional complementary and integrative medicine (TCIM) as part of their cancer and survivorship care. Published studies from around the world report increasing use of TCIM by people living with cancer. This article summarizes the presentations that took place during a symposium titled, "Integrative Oncology: International Perspectives" at the International Research Congress on Integrative Medicine and Health i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 52 publications
0
40
0
7
Order By: Relevance
“…Moreover there is evidence that orally taken medicinal mushrooms have an influence on the microbiome (Friedman, 2016;Jayachandran et al, 2017;Grant et al, 2019). Medicinal mushrooms could act as prebiotics that can stimulate the growth of beneficial microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover there is evidence that orally taken medicinal mushrooms have an influence on the microbiome (Friedman, 2016;Jayachandran et al, 2017;Grant et al, 2019). Medicinal mushrooms could act as prebiotics that can stimulate the growth of beneficial microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The use of complementary and integrative medicine (CIM) is widespread and widely accepted in cancer patients (Astin, 1998;Ernst and Cassileth, 1998). Studies have shown that 20-50% of cancer patients use some form of CIM therapies as an add-on to conventional treatments (Ernst and Cassileth, 1998;Grant et al, 2019). Medicinal mushrooms have been used in traditional Asian medical systems continually for several centuries (Wasser, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…12 In a recent review of global trends for the utilization of integrative medicine in oncology, the authors document that 22% of oncology centers in European countries and up to 65% in Australian are now using integrative medicine, with acupuncture often being the most commonly used therapy. 13…”
Section: Integrative Healthmentioning
confidence: 99%
“…In addition, recent programs have been developed to improve CM in oncology settings. [37][38][39] The third barrier, variable access to CM at this hospital, was in part based on the fact that some CMs were not covered by mandatory basic health insurance. Indeed, in 2006, 58% of CM costs in Swiss hospitals were covered by mandatory basic health insurance, 28% by complementary health insurance, and 9% directly by patients.…”
Section: Assessment Of Current Practicementioning
confidence: 99%